Growth and Yield Response of Soybean (Glycine max L. Merr.) to NPK and Eco-Enzyme Application - Edi Wirman Wirman; Syaifuddin Islami Islami; Indah Permata Sari Indah (Universitas Muhammadiyah Mataram, 2025)
The study aimed to obtain the interaction of NPK and ecoenzymes on the growth and yield of soybean plants, thus reducing the use of NPK. The experiment was conducted on dry land in Kuranji-Padang, at an altitude of 10 m above sea level, from May to August 2023. The study used a factorial completely randomized design (CRD) (4 x 3) with 3 replications. The first factor was ecoenzyme consisting of 3 levels; 0, 5, 10, and 15 ml/l water. The second factor is NPK which consists of 3 levels, namely; 100, 200, and 250 kg/ha. Parameters observed; plant height, number of primary branches, number of leaves, number of effective root nodules, number of pods per plant, number of empty pods, pod length, 100 seed weight, and dry weight of seeds/plot. Data were investigated for variance, if the effect was significant, it was followed by the 5% level of Honest Real Difference (BNJ) test. Data were analyzed using Statistix software ver. 8. The results showed a significant interaction between NPK 200 kg/ha with 0 ml/l ecoenzyme on the growth of soybean plant height. NPK at 200 kg/ha significantly affected the number of primary branches, the number of pods, and the dry weight of seeds/plot. Ecoenzyme was not significant on the number of primary branches, number of leaves, number of root nodules, or pod length of soybean plants. Optimization of ecoenzymes needs to be done by reducing the rate of NPK fertilizer given.